2011
DOI: 10.1002/jbio.201100058
|View full text |Cite
|
Sign up to set email alerts
|

Membrane composition of jetted lipid vesicles: a Raman spectroscopy study

Abstract: Microfluidic jetting is a promising method to produce giant unilamellar phospholipid vesicles for mimicking living cells in biomedical studies. We have investigated the chemical composition of membranes of vesicles prepared using this approach by means of Raman scattering spectroscopy. The membranes of all jetted vesicles are found to contain residuals of the organic solvent decane used in the preparation of the initial planar membrane. The decane inclusions are randomly distributed over the vesicle surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 19 publications
3
27
0
Order By: Relevance
“…This oil fraction is low enough, however, not to affect the membrane thickness. In comparison, other studies on IE-prepared liposomes reported the presence of <5% of oil in the bilayer (30) or of hydrophobic residues when decane is used instead of oil (46). Considering our results on IE liposomes, PMS from cells, or EF liposomes with added oil, the central point of our study is that it demonstrates that a low fraction of hydrophobic compounds in the lipid bilayer dramatically alters membrane dynamics.…”
Section: Resultssupporting
confidence: 47%
“…This oil fraction is low enough, however, not to affect the membrane thickness. In comparison, other studies on IE-prepared liposomes reported the presence of <5% of oil in the bilayer (30) or of hydrophobic residues when decane is used instead of oil (46). Considering our results on IE liposomes, PMS from cells, or EF liposomes with added oil, the central point of our study is that it demonstrates that a low fraction of hydrophobic compounds in the lipid bilayer dramatically alters membrane dynamics.…”
Section: Resultssupporting
confidence: 47%
“…Performing the same experiments with a membrane model, Giant Unilamellar Vesicles (GUV), which is a lipid bilayer with a size similar to that of cells44, would allow to focus only on the interaction between pulsed electric fields and a lipid bilayer. Acquiring the Raman signatures of GUVs has already been done with a similar confocal Raman microspectroscope45. The acquisition of the Raman spectra in the HWN region was also used to monitor the transmembrane potential of cells4647.…”
Section: Resultsmentioning
confidence: 99%
“…62 Nevertheless, complementary techniques like jetting produce vesicles that appear oil-free by optical microscopy, but can contain decane layers or lenses ~10 nm thick. 63 Thin layers or lenses of oil may be inconsequential in some applications and detrimental in others. For example, Campillo et al pulled nanotubes both from vesicles made by a reverse emulsion technique and from vesicles made by electroformation.…”
Section: Discussionmentioning
confidence: 99%